Observations and possibilities: are the historical observations of community colleges applicable in the operation of present-day community colleges? (Training and Practice : Journal of Educational Sciences, 2017)
The community colleges came into existence in Denmark in the middle of the 19th century originally with the aim of providing available alternative for the rural adult population excluded from education to be able to catch up with the social and economic challenges of the era. The method and the instituion proved to be a success story both in Denmark and in the following decades first of all in Scandinavia, which has still been going on unbeaten.Attempts to establish educational institutions of similar type were made in Hungary as well between the two world wars but their success was altering significantly. In our lecture we would like to make attempts to reveal some determining factors which made the success of Hungarian community colleges altering in the era, but at the same time to compare all this with the present practice of community colleges examining the question whether the principles, practice and experience of the period between the two world wars may be used in the changed social, ecoonomic, educational/teaching/learning environment during the establishment of an optimal organisational, operational system.According to our observations this approach makes our research up-to-date. Our key issues in the focal point are (comparing the 20ies – 30ies to the practice of today): to what extent the circle of founders, actuators, the composition of the target group, the maintainers, financing, the functions of the organizations, the educational aims, contents, methods, the forms of education changed in the different types of community colleges. We have examined the geographical location, distribution of the institutions, the characteristic features of the settlements and their configuration, accessibility, which may be a sore point in view of the fact that – contrary to the classical Scandinavian community colleges - boarding schools are quite rare types in Hungarian practice. We have used archival sources, analysed specialized literature, done research work, used statistical data and own research results as well.